Biogeochemical dynamics at major river-coastal interfaces : linkages with global change - Bianchi, Thomas S.; Allison, Mead A. (Mead Ashton); Cai, Wei-Jun, 1960- (Cambridge University Press, 2014)
State-of-the-art, comprehensive synthesis of biogeochemical dynamics and impact of human alterations at major river-coastal interfaces for advanced students and researchers.